Service value and switching barriers: a personal values perspective. Issue 3 (11th March 2016) - Thuy, Pham Ngoc; Hau, Le Nguyen; Evangelista, Felicitas
ABSTRACT: This research aims to investigate how customers, the key actors in a service relationship, perceive service value and switching barriers. The study is framed along the means-end-chain theory of personal values and theory of customer resources in the service-dominant logic. Hypotheses about the impact of personal values on customer value, switching barriers and customer loyalty were tested using structural equation modeling of survey data obtained from the health care and retail banking sectors in Vietnam. The results show that in both sectors, personal values have a significant impact on perceived process and outcome value as well as on perceived economic and relational switching barriers. Economic barriers were found to affect loyalty in the banking sector, in the same way that relational barriers affect loyalty in the health-care sector only. Loyalty in both sectors is influenced by process but not by outcome value. The implications of these findings are discussed.